A technical consideration when using flow diversion for recurrent aneurysms following stent-assisted coiling. (15th November 2016) - Mascitelli, Justin R; Wei, Daniel; Oxley, Thomas J; Kellner, Christopher P; Shoirah, Hazem; De Leacy, Reade A; Mocco, J; Fifi, Johanna T
Abstract : Flow diversion (FD) is a treatment option for recurrent aneurysms including following stent-assisted coiling (SAC), although this approach is both 'off-label' and unproven. A technical challenge of FD placement may involve the microwire catching on the tines of the previously placed stent or potentially going 'in-out-in' from the central axis of the stent. We report a case and technique that assures the wire has safely remained within the central axis of the stent. The procedure was performed in standard fashion except that the intermediate catheter was passed completely through the previously placed stent after the microwire/microcatheter had crossed. The large diameter of the intermediate catheter assured that the microwire did not go 'in-out-in'. The intermediate catheter was completely withdrawn from the stent and the FD was placed in standard fashion. This technique may help to achieve complete FD opening and prevent thromboembolic complications associated with incomplete FD opening.